Knowledge, anxiety, stress and COVID-19 guidelines practice among nursing students: a cross-sectional study - Budury, Syiddatul; Fitriasari, ndikawati; Pramesti, Theresia Anita; Eka Sari, Diah Jerita; Widiharti , Widiharti (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the relationship of knowledge, anxiety and stress with the practice of coronavirus disease-2019 guidelines among nursing students. Method: The cross-sectional study was conducted in June-July 2020 after approval from the ethics review board of Universitas Nahdlatul Ulama, Surabaya, Indonesia, and comprised undergraduate nursing students in their second, third and fourth years of studies at various universities in the East Java region. Data was collected using the Depression, Anxiety, Stress Scale-21 questionnaire. Knowledge about coronavirus disease-2019 guidelines was assessed using a self-developed questionnaire in line with World Health Organisation advisory. Data was analysed using SPSS 25. Results: Of the 227 subjects, 204(90%) were women and 23(10%) were men. The overall mean age was 20.10±1.5888 years. There was no significant association of knowledge, anxiety and stress with the practice of coronavirus disease-2019 guidelines (p>0.05). Conclusion: Adequate knowledge of coronavirus disease-2019 did not make the nursing students follow the relevant guidelines. Keywords: Nursing, Anxiety, Mental health, Socialisation, Stress, COVID-19. (